2019
DOI: 10.26502/jppch.74050021
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Extemporaneous Glucocorticoid Formulations and Doses for Asthma-like Symptoms in Children

Abstract: Treatment strategies for asthma-like symptoms are challenging with no international consensus on dose of systemic glucocorticoids. Despite, asthma-like symptoms remain one of the most common medical conditions seen in infants and preschool children. This is further complicated by limited licensed preparations and use of various extemporaneously prepared formulations in some countries. In Denmark, all extemporaneous formulations are produced according to GMP, which is different from other European countries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The previous study observed variations in the extemporaneous glucocorticoid for asthma therapy in children. It was confirmed to affect the length of hospitalization and other adverse effects (12 cases found) [ 38 ]. Therefore, it is necessary to establish standards for the compounding process, including standard formulas, appropriate equipment, and trained personnel [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous study observed variations in the extemporaneous glucocorticoid for asthma therapy in children. It was confirmed to affect the length of hospitalization and other adverse effects (12 cases found) [ 38 ]. Therefore, it is necessary to establish standards for the compounding process, including standard formulas, appropriate equipment, and trained personnel [ 39 ].…”
Section: Resultsmentioning
confidence: 99%